2004
DOI: 10.1001/archderm.140.7.827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Superpotent Melanotropic Peptide in Combination With Solar UV Radiation on Tanning of the Skin in Human Volunteers

Abstract: Three phase 1 clinical trials of a superpotent melanotropic peptide, melanotan-1 (MT-1, or [Nle 4 -D-Phe 7 ]␣-melanocyte-stimulating hormone) were performed to demonstrate safety for MT-1 therapy combined with UV-B light or sunlight. Design: Open-label studies at 2 dose levels of MT-1 combined with small doses of UV-B to the neck or buttock or full sunlight to half of the back.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Although the exact role for ␣-MSH in melanoma cell migration remains unclear, our findings suggest that regulation syndecan-2 expression by ␣-MSH plays a crucial role in the migration of melanoma cells. Recent clinical studies have shown that a potent synthetic analogue of ␣-MSH, NDP-MSH, significantly increases the eumelanin content of human skin (42). Interestingly, ␣-MSHmediated syndecan-2 expression occurs independently of melanin synthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact role for ␣-MSH in melanoma cell migration remains unclear, our findings suggest that regulation syndecan-2 expression by ␣-MSH plays a crucial role in the migration of melanoma cells. Recent clinical studies have shown that a potent synthetic analogue of ␣-MSH, NDP-MSH, significantly increases the eumelanin content of human skin (42). Interestingly, ␣-MSHmediated syndecan-2 expression occurs independently of melanin synthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that such a combined antiinflammatory and antifibrogenic activity of MSH peptides in the treatment of scleroderma would be welcome. Human toxicity studies in which 0.08 mg/kg of NDP-␣-MSH was given subcutaneously revealed only minor side effects (e.g., nausea and transient facial flushing) (45). Indeed, hyperpigmentation is a known effect of ␣-MSH and related peptides (46).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1960s, Lerner and McGuire discovered that injections with αMSH, one of the MC1R agonists (see Figure 2), increased human skin pigmentation [77]. More recently, several studies examined the effects of [Nle 4 -D-Phe 7 ]-αMSH, a synthetic superpotent analogue of αMSH, on human skin in situ and reported increased pigmentation after a series of 10 injections [78][79][80][81]. In a larger study, injections of 65 subjects with a slow-release formulation of the same αMSH analogue over 3 months lead to an average 41% increase of melanin in subjects with high sun-sensitivity compared to a 12% increase in subjects with low sun-sensitivity, and there was no significant difference in pigmentation between sun-exposed and non-sun-exposed areas [82].…”
Section: Stimulation Of Melanogenesismentioning
confidence: 99%